1978
DOI: 10.1021/ja00489a046
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes upon oxygenation of an iron(II)(porphyrinato)(imidazole) complex

Abstract: Structural Changes upon Oxygenation of an Iron(II)(porphyrinato)(imidazole) Complex Sir:Structural effects of metal ligation are a central theme of metalloporphyrin stereochemistry.1 Of particular interest in interpreting structure/function relationships of hemoproteins are precisely determined, five-coordinate, imidazole porphyrinato iron(II) complexes and their dioxygen adducts. We report here the structure of such a five-coordinate complex2•3 Fe(TpivPP)(2-Melm)-C2H50H, I (Figure 1), and its sixcoordinate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
94
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 1 publication
12
94
1
Order By: Relevance
“…As the size of the E7 amino acid is increased from Gly to Phe, decreases in k O2 , In 1970, Perutz (1) proposed that the distal histidines located at the E7 helical positions, 3 ␣His-58 and ␤His-63, play crucial structural roles for regulating both the affinities and rates of O 2 binding to adult human hemoglobin (HbA). 4 These ideas were based on the suggestion by Pauling (2) that His(E7) could stabilize bound O 2 by donating a hydrogen bond to the partial negative charge on the superoxide-Fe(III)-like FeO 2 complex and on the idea by Perutz and Mathews (3) that the distal histidine could also be acting as gate for ligand entry and exit. Studies of model heme compounds and naturally occurring globins with His(E7) replacements suggested strongly that the distal histidine also plays a key role in discrimination between O 2 and CO binding (4 -9).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As the size of the E7 amino acid is increased from Gly to Phe, decreases in k O2 , In 1970, Perutz (1) proposed that the distal histidines located at the E7 helical positions, 3 ␣His-58 and ␤His-63, play crucial structural roles for regulating both the affinities and rates of O 2 binding to adult human hemoglobin (HbA). 4 These ideas were based on the suggestion by Pauling (2) that His(E7) could stabilize bound O 2 by donating a hydrogen bond to the partial negative charge on the superoxide-Fe(III)-like FeO 2 complex and on the idea by Perutz and Mathews (3) that the distal histidine could also be acting as gate for ligand entry and exit. Studies of model heme compounds and naturally occurring globins with His(E7) replacements suggested strongly that the distal histidine also plays a key role in discrimination between O 2 and CO binding (4 -9).…”
mentioning
confidence: 99%
“…For example, His(E7) refers to the histidine at the seventh position along the E-helix, which in the ␣ and ␤ subunits are His-58 and His-63, respectively. 4 The abbreviations used are: HbA, adult human hemoglobin; WT, wild type; FTIR, Fourier-transform infrared spectroscopy. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 A structural basis for discrimination against CO was suggested based on the crystal structures of MbCO which seemed to indicate that the protein forces CO to bind in a bent Fe-C-O geometry. 5 It was found that CO binds to model hemes with a linear Fe-C-O geometry 6 but binds to Mb in a bent geometry, 5 and that O 2 binds to model hemes [7][8][9] and Mb with a similar bent Fe-O-O geometry. 10 Considering that the O 2 prefers to bind to the heme in a bent geometry, which is unaffected by the Mb, it was presumed that the protein forces CO to bind in a bent geometry, thereby reducing the affinity of the heme in Mb for CO relative to O 2 .…”
Section: Introductionmentioning
confidence: 99%